PANDE MAS DAN PERKEMBANGAN GAYA SENI RELIEF PADA PERHIASAN MASA KLASIK AKHIR DI JAWA - Ari Supriyanto (Institut Seni Indonesia Surakarta, 2014)
Jewelry in this study, is one of the ancient Javanese artefacts from late classical period, made by an expertin the field of jewelry which is called pande mas. Gold jewelry from late classical period in Java can be foundin the National Museum in Jakarta. The purpose of this research paper is to know about the development ofgold jewelry, especially jewelry that has a relief of the classical period late in Java, and know the variousfactors behind them are related to one another. In connection with the various things that have to be revealedbehind the visual jewelry appropriately and correctly, then the writing of this research is a qualitative study,using a multidisciplinary approach.Keywords: Pande mas, jewelry in Java, late classical period.